THE RECIPROCAL RELATIONSHIP BETWEEN PROFITABILITY AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Prastiwi, Arum; Atmini, Sari; Pusposari, Devy; Martika Sari, Yetri; Christinawati Putri, Ferica (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
The relationship between CSR disclosure and financial performance remains contentious, particularly in emerging market resource sectors. This study examined the bidirectional relationship between CSR disclosure and profitability in Indonesian oil and gas mining companies from 2012 to 2019 using panel data regression on nine listed firms, yielding 69 observations. CSR disclosure was measured using GRI-G4 indicators, while profitability was assessed through ROA, ROE, NPM, and EPS, with firm size and leverage as controls. The analysis revealed significant reciprocal relationships with contrasting patterns. ROA and NPM showed negative bidirectional relationships with CSR disclosure, suggesting trade-offs between operational efficiency and social transparency. Conversely, ROE and EPS demonstrated positive reciprocal relationships, indicating CSR alignment with shareholder returns. These findings suggest companies should view CSR as a strategic investment, while regulators need stronger frameworks to promote synergy between financial sustainability and responsible disclosure.